Subjective Well-Being and Partnership Dynamics: Are Same-Sex Relationships Different? - Shuai Chen; Jan C. van Ours (Institute of Labor Economics (IZA), 2017)
Partnered individuals are happier than singles. This can be because partnership leads to more satisfactory subjective well-being or because happier people are more likely to find a partner. We analyze Dutch panel data to investigate whether there is a causal effect of partnership on subjective well-being. Our data allow us to distinguish between marriage and cohabitation and between same-sex partnerships and opposite-sex ones. Our results support the short-term crisis model and adaptation theory. We find that marital partnership improves well-being and that these benefits are homogeneous to sexual orientation. The well-being gains of marriage are larger than those of cohabitation. Investigating partnership formation and disruption, we discover that the well-being effects are symmetric. Finally, we find that marriage improves well-being for both younger and older cohorts while cohabitation only benefits younger cohort.
Keywords: J12; 330; subjective well-being; happiness; marriage; cohabitation; sexual orientation